Pesquisadores em estimulação magnética transcraniana no Brasil - Silva Júnior, Hercílio Barbosa (2017)
The research investigate the data related to the researchers work on Transcranial Magnetic Stimulation in Brazil, as well as the groups, lines, research projects and areas of knowledge that are involved with the subject.